ION EXCHANGE COLUMN PERFORMANCE MODE LFOR SEPARATION OF ZIRCONIUM AND HAFNIUMIN ADSORPTION PROCESS - Moch. Setyadji; Endang Susiantini (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2015)
ION EXCHANGE COLUMN PERFORMANCE MODE LFOR SEPARATION OF ZIRCONIUM AND HAFNIUMIN ADSORPTION PROCESS. Amathematicalmodel for the separation of zirconium (IV) and Hafnium (IV) in the fixed bed column containing anion exchange resin Dowex-1X8 have been developed. The purpose of this experiment was to validate the mathematical model that will be used to determine (verify) the effective axial diffusivity, overall mass transfer coefficient and zirconium-hafnium separation factor. The flow in the column was assumed to follow plug flow. Zirconium and hafnium transfered from liquid phase to solid phase. In this experiment, zirconium and hafnium separation was studied using anion exchange resin (Dowex-1X8) in batch and fixed bed column processes. Batch process experimentswere carried out to determine the adsorption equilibrium constants, while the continuous process experiments were carried out to determine the effective axial diffusivity coefficient (Dez) and overall mass transfer coefficient (kc.a). The values of Dez and kc.a were determined by taking certain values so that the simulation results of zirconium and hafnium concentrations in the solution (C) and in the adsorbent (X) at any time on any element of column compared with concentrations of laboratory data were similar. The results showed that the adsorption equilibrium of complex compounds of zirconium and hafnium sulphate on Dowex-1X8 anion resin approached by Henry’s equilibriummodel with values, HZr = 0.089 L/g resin dan HHf = 0.130 L/g resin. The separation factor of Zr-Hf Zr-Hf =1.924 for 14.7 cm.Mathematicalmodel based on Henry’s equilibrium constants to simulate zirconium and hafnium concentrations out of the fixed bed ion exchange column could fit the experimental data very well with maximum average relative error of 17.962%.